The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1111/j.1365-2362.1994.tb02419.x
|View full text |Cite
|
Sign up to set email alerts
|

The megakaryocyte platelet system and vascular disease

Abstract: Platelets form a heterogeneous population of cells produced from the uniquely large polyploid cell found in the bone marrow, the megakaryocyte. The platelet megakaryocyte axis forms a dynamic equilibrium varying in normal biology and in disease. Prolonged platelet destruction leads to the production of large platelets from large, high ploidy megakaryocytes. In vivo and ex vivo studies show that such platelets have more haemostatic potential than smaller less dense platelets. The evidence suggesting that prothr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
2

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 109 publications
(88 reference statements)
1
24
0
2
Order By: Relevance
“…We wish ' to comment on fundamental concepts that have arisen in recent years. Our results support the concept of &dquo;hyperactive prethrombotic platelets&dquo; (30,31) and support the superb hypothesis of the role of the megakaryocyte in controlling platelet function (7,32).…”
Section: Discussionsupporting
confidence: 86%
“…We wish ' to comment on fundamental concepts that have arisen in recent years. Our results support the concept of &dquo;hyperactive prethrombotic platelets&dquo; (30,31) and support the superb hypothesis of the role of the megakaryocyte in controlling platelet function (7,32).…”
Section: Discussionsupporting
confidence: 86%
“…Because platelets do not have a nucleus, only residual amounts of mRNA, and limited protein synthesis (9), the presence of ER-␣ and ER-␤ in megakaryocytes (in the nucleus and cytoplasm) from both groups indicates that ovarian hormones, including 17␤-estradiol, may be involved in modulating content of growth factors genomically in megakaryocytes. ER-␤ may be the main ER in porcine platelets because platelets from both groups had more extensive positive immunofluorescence staining to ER-␤ than to ER-␣.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, platelets originating from high-ploidy MKs are thought to be more easily activated than platelets generated from MKs with a lower ploidy. 11 Therefore, polyploidy may regulate gene expression, MK maturation, and consequently platelet function. 12 In favor of this hypothesis, it has been demonstrated that polyploidization up-or down-regulates gene expression of a small number of genes in yeast.…”
Section: Introductionmentioning
confidence: 99%